PENGARUH TIPE COOPERATIVE SCRIPT TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SEKOLAH DASAR - Budi, Virgi Setia; Syambasril, Syambasril; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze the effect of the application of cooperative script on the results of reading comprehension skills of class V students of Western Pontianak 55 Elementary School. The method used is the experimental method, while the form of research used is quasi experimental design with nonequivalent control group design. The population and sample in this study were all fifth grade students of Western Pontianak 55 Elementary School. The data collection tool used was a multiple choice test with 26 questions. Based on data analysis, the average post-test results of the experimental class were 73,06 while the average post-test results of the control class were 67,79. The results of the t test are obtained tcount of 2,124 and t table α = 5% (with dk = 32 + 28 - 2 = 58) of 2,001, which means tcount (2,124)> t table (2,001), then the alternative hypothesis (Ha) is accepted. It can be concluded that there is influence the application of cooperative script on the results of reading comprehension skills of class V students of Western Pontianak 55 Elementary School. From the results of the calculation of the effect size (ES) ES obtained is 0,4466 (medium criteria). This means that the application of cooperative script a good influence on the results of reading comprehension skills of class V students of Western Pontianak 55 Elementary School Keywords: cooperative script, reading comprehension skills